Zinc protoporphyrin IX attenuates closed head injury-induced edema formation, blood-brain barrier disruption, and serotonin levels in the rat - Vannemreddy P.; Ray A.K.; Patnaik R.; Patnaik S.; Mohanty S.; Sharma H.S. (My University, 2025)
The role of heme oxygenase (HO) in closed head injury (CHI) was examined using a potent HO and guanylyl cyclase inhibitor, zinc protoporphyrin (Zn-PP) in the rat. Blood-brain barrier (BBB) permeability to Evans blue and radioiodine, edema formation, and plasma and brain levels of serotonin were measured in control, CHI, and Zn-PP-treated CHI rats. CHI was produced by an impact of 0.224 N on the right parietal bone by dropping 114.6 g weight from a height of 20 cm in anesthetized rats. This concussive injury resulted in edema formation and brain swelling 5 hours after insult that was most pronounced in the contralateral hemisphere. The whole brain was edematous and remained in a semi-fluid state. Microvascular permeability disturbances to protein tracers were prominent in both cerebral hemispheres and the underlying cerebral structures. Plasma and brain serotonin showed pronounced increases and correlated with edema formation. Pretreatment with Zn-PP (10 mg/ kg, i.p) 30 minutes before or after CHI attenuated edema formation, brain swelling, plasma and brain serotonin levels, and microvascular permeability at 5 hours. Brain edema, BBB permeability, and serotonin levels were not attenuated when the compound was administered 60 minutes post-CHI suggesting that HO is involved in cellular and molecular mechanisms of edema formation and BBB breakdown early after CHI. © 2006 Springer-Verlag.